Contribution to the systematics of dicerataspis ashmead, 1896 (Hymenoptera: Cynipoidea: Figitidae) - Gallardo, Fabiana Edith (2010)
This paper deals with the identity, geographical distribution and host associations of Dicerataspis species. The authors propose the new synonymy Dicerataspis grenadensis Ashmead, 1896 (= D. flavipes Kieffer, 1909) and redescribe and illustrate D. grenadensis.